CHARACTERISTICS OF WASTEWATER IMMERSION MEMBRANE BIOREACTOR - , П. В. (Municipal economy of cities (Technical science), 2013)
The experience of operating a membrane bioreactor (MBR) for wastewater treatment, analysis of the main indicators of the effectiveness of ICBMs.